PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR AL-QUR'AN HADITS: Implementasi di MAN I Muntok - Anwar, Muhammad Rofiq (Tarbawy : Jurnal Pendidikan Islam, 2022)
The learning model is a means of increasing learning activities in the classroom, one of which is the Contextual Teaching and Learning model. This study aims to examine the effect of the Contextual Teaching and Learning Model on Student Learning Outcomes to Class X MAN 1 West Being. The research method used is a quantitative method, using experiments, as a data analysis technique. The results of the instrument validation show the test item reliability coefficient of 0.752. The results of data analysis show that there is a positive and significant influence between the use of the contextual teaching and learning (CTL) learning model on learning outcomes of the Qur'an Hadith. The results of data analysis whereby calculating the average results on each test in the experimental class and control class showed an increase between before the implementation of the learning model and after the implementation of the learning model, namely 38.09 to 80.47 for the experimental class and 35.71 to 68.09 for the control class. Then the comparison between the experimental and control classes was very significant, namely 28.05 and 14.96, so the effect of using the contextual teaching and learning (CTL) learning model on learning outcomes was greater than the class that did not use the CTL model.